ChemInform Abstract: Computationally Driven Reassignment of the Structures of Aldingenins A and B. Issue 48 (December 2015) - Mukhina, Olga A.; Koshino, Hiroyuki; Crimmins, Michael T.; Kutateladze, Andrei G.
Abstract: Aldingenin A is assigned the structure of 5‐(S)‐hydroxycaespitol (I) and aldingenin B the structure of hemiacetal (II).